Self-management as a means of professional development of future teachers - Дуднік, Ніна Юріївна (Pedagogy of Higher and Secondary Education, 2013)
Dudnik N. Yu. Self-management as a means of professional development of future teachers. The article deals with the essence of the concept of «Self-management» in modern literature and determines its role in the professional development of the individual; the results of research to identify the importance of self-management skills for future teachers are exemplified. The article emphasizes the need to develop students’ skills of self-management for professional formation and development.